Symposium on the privatisation of state assets and state commercial companies - Cassells, Peter (Statistical and Social Inquiry Society of Ireland, 1988)
In a recent article in the Irish Times (November 5 1987) Political Editor Dick Walsh pointed out that "calling for privatisation now sounds like a singularly ill-timed appeal to give capitalism another chance. It sounds ill-timed because behind the argument for privatisation lies the assumption that the market-place offers us the prospect of a brighter future better use of our resources, less strain on public funds, greater efficiency in the supply of goods and services than we've known so far."
The privatisation of state assets and state commercial companies
Read before the Society, 3 December 1987
Keywords: Privatisation; Semi-state companies; 314.15